Study on the effect of zeolite rice husk particles on polysulfone membrane - Rosman, Nurafiqah (2015)
Rice Husk Zeolite Type Y (RHY) particles were prepared under static hydrothermal conditions by dissolution of sodium hydroxide (NaOH), sodium aluminate (NaAlO2) and amorphous silica obtained from rice husk ash (RHA). The RHY/polysulfones (PSf) membranes incorporated with RHY particle at different loading were prepared through phase inversion technique. Physical characterization were carried out using thermogravimetric analysis (TGA), scanning electron microscope (SEM), porosity, tensile strength, atomic force microscope (AFM) and water contact angle (CA). The X-ray diffraction (XRD) analysis confirmed the transformation of RHA into zeolite type Y supported with Field Emission Scanning electron microscopy (FESEM) image and Energy dispersive X-ray spectroscopy (EDX). The EDX analysis showed that the Si/Al ratio was 2.007 which indicate the zeolite products is in hydrophilic condition. Meanwhile, the performance of the fabricated membrane was evaluated through pure water permeation (PWP), rejection and antifouling properties. The membranes with 2wt% of RHY showed the highest water permeability (315.29 Lm-2h-1), hydrophilicity (45o) porosity (41.5%) and good rejection (97.8%) ability. Membranes with higher RHY content (more than 2wt. %) generated more particle agglomeration that disturbs membrane structure as can be observed in the cross-section and external surface morphology. In fact, the excessive amount of RHY particles caused deduction of membrane permeation, compared to the pristine membrane which indicated the ability of membrane to absorb the foulants. The incorporation of RHY (1 to 5wt. %) increase the humic acid rejection from 95.8 to 99.6 %. It also found that PSf-RHY membrane having higher absorptive and fouling values than pristine PSf membrane. It can be concluded that the addition of RHY could enhance the hydrophilicity of the PSf membrane with optimum value of 2 wt.%. However, the addition of RHY need to be properly controlled as the high RHY loading could create an adverse effect for the foulants.